Financing Thai SMEs in the pandemic era - Pitakdumrongkit, Kaewkamol (2020)
The Thai government rolled out schemes to finance SMEs and help them weather the impact of the COVID-19 pandemic. While these programmes have some merits, there are ways to improve them.